2018
DOI: 10.1177/1082013218784389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of xylitol and stevioside on the physical and rheological properties of gelatin from cod skin

Abstract: Jelly and confectionery products are high in sugar and calories. Xylitol and stevioside are natural low-calorie sweeteners and they can be used as an alternative; however, their effects on fish gelatin are unknown. The gelatin was extracted from cod skins and added to xylitol or stevioside (0, 2, 6, 10, 14, and 20% (w/v)) to form gel products. This paper investigated how xylitol and stevioside affected the physical and rheological behaviors of fish gelatin, such as color, gel strength, texture profile analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…The observed behavior against the temperature is typical to previously studied fish skin gelatin extracted from Catla catla (Chandra & Shamasundar, 2015). Similar to our findings, the cod skin gelatin showed gelling/melting temperatures of 21.2 and 27.4°C, respectively (Cai et al, 2018). However, after peptides addition, these values significantly changed and the resulting bioactive gelling solution acquired new gelling and melting points of 20.5 and 21.9°C, respectively.…”
Section: Rheological Propertiessupporting
confidence: 90%
“…The observed behavior against the temperature is typical to previously studied fish skin gelatin extracted from Catla catla (Chandra & Shamasundar, 2015). Similar to our findings, the cod skin gelatin showed gelling/melting temperatures of 21.2 and 27.4°C, respectively (Cai et al, 2018). However, after peptides addition, these values significantly changed and the resulting bioactive gelling solution acquired new gelling and melting points of 20.5 and 21.9°C, respectively.…”
Section: Rheological Propertiessupporting
confidence: 90%
“…The higher melting temperatures compared with the gelling temperatures are an indication of reluctance to the thermoreversible gel-sol transition that is characteristic of polymeric dispersions (Huang et al, 2017). Similar results and behavior pattern were obtained for cod gelatin in other works reported in literature (Cai et al, 2018;Fernández-Dıáz et al, 2001;Gomez-Guillen et al, 2002;Nian et al, 2018).…”
Section: Tablesupporting
confidence: 86%
“…Xylitol is a nutritive, naturally occurring sweetener (a sugar alcohol) generally present at very low concentrations in various vegetables and fruits (such as raspberry, lettuce, cabbage, broccoli, cauliflower, grape, strawberry, and banana), mushroom, yeast, seaweed, and lichen (Piątek-Hnat & Bomba, 2020). It is used as a functional sweetener in low-sugar food and has been reported to decrease acidogenic bacteria and inhibit their growth and biofilm formation (Cai et al, 2018). A review on the antimicrobial activity of xylitol by de Oliveira et al (2018) showed that it could eradicate both vegetative and biofilm cells of Staphylococcus epidermidis and S. aureus.…”
Section: Lf and Xylitolmentioning
confidence: 99%